2013
DOI: 10.1016/j.tvjl.2013.01.028
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the dynamics of bovine corona virus and respiratory syncytial virus infections in dairy herds

Abstract: The objective of this study was to examine the dynamics of bovine corona virus (BCV) and bovine respiratory syncytial virus (BRSV) infections in dairy herds over a 3-year period. The status of 79 dairy herds located in two Northern and two Southern Regions of Sweden were surveyed by measuring antibody concentrations to BCV and BRSV in pooled milk samples from primiparous cows, and in bulk-tank milk twice annually. In the Southern Regions the percentage of antibody-positive herds remained persistently high (75-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
5
29
0
Order By: Relevance
“…1,12 In the present study, all 15 diseased and EqCoV qPCR-positive horses had evidence of specific antibodies to EqCoV in the convalescent serum samples, which reflects the high sensitivity of the S protein-based ELISA. The present ELISA was based on recombinant S protein of EqCoV because of the technical difficulty in growing large amounts of EqCoV.…”
Section: Equid Herpesvirus 1 Equid Herpesvirus 4 Equine Influenza Asupporting
confidence: 54%
“…1,12 In the present study, all 15 diseased and EqCoV qPCR-positive horses had evidence of specific antibodies to EqCoV in the convalescent serum samples, which reflects the high sensitivity of the S protein-based ELISA. The present ELISA was based on recombinant S protein of EqCoV because of the technical difficulty in growing large amounts of EqCoV.…”
Section: Equid Herpesvirus 1 Equid Herpesvirus 4 Equine Influenza Asupporting
confidence: 54%
“…Regarding the prevalence of BCoV, serological surveys indicate that approximately 90% of the worldwide cattle population has Abs against BCoV 8 . However, Ohlson et al 31 observed that BCoV Ab-positive herds remained persistently high (75---100%) in Swedish Southern regions compared with Northern regions where the percentage of positive herds were lower (38---80%). In Argentina, 100% of the adult cattle population is estimated to be seropositive for Abs to CoVB (Dr. Parreño, personal communication).…”
Section: Introductionmentioning
confidence: 97%
“…The incidence of BCoV varies between 15% and 70% in naturally occurring outbreaks worldwide 25,27,31 . In the Southern hemisphere, Al Mawly et al 1 detected a BCoV prevalence of 14% during 2011 calving season in dairy farms in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission dynamics for BCV has not yet been investigated in Norway, although one study describes a regional outbreak of winter dysentery (Toftaker et al, 2017). Studies from Sweden have shown that recent BCV infection is common, indicating that the infection is easily transmitted (Beaudeau et al, 2010;Ohlson et al, 2013). Due to the constant risk of virus introduction, the assumption that a negative status is valid for a long time is questionable.…”
Section: Introductionmentioning
confidence: 99%